The "Intertextuality" In the Maghrebine novel - Bouali, Abderrahmane Abdellah (Al-Adab Journal, 2020)
The concept of "intertextuality" as a new central critical concept occupied the efforts of many researchers, scholars and critics, Western and Arab, until it became a concept around which research and studies revolve, and indeed it became an important field of criticism, and it actually constitutes a tool of high-importance discourse analysis tools. The concept of "intertextuality" in the novel occupied a remarkable space. In this research, we have chosen a set of Arab and Maghrebian novels to analyze the notion of literary "intertextuality". The novels chosen are: "The departure of the sea" by the Moroccan Mohamed Ezzedine Tazi, "the secrets of the owner of the concealment" by the Tunisian Ibrahim Dargouthi, "the fragmented mirrors" by the Algerian Abdel Malek Murthadh, "Al Tibr" by Libyan Ibrahim Al Kaouni.